Impact of exercise on articular cartilage in people at risk of, or with established, knee osteoarthritis: a systematic review of randomised controlled trials. Issue 15 (22nd June 2018) - Bricca, Alessio; Juhl, Carsten B; Steultjens, Martijn; Wirth, Wolfgang; Roos, Ewa M
Abstract : Objective: To investigate the impact of knee joint loading exercise on articular cartilage in people at risk of, or with established, knee osteoarthritis (OA) by conducting a systematic review of randomised controlled trials (RCTs). Design: We followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Data sources: We performed a literature search with no restriction on publication year or language in MEDLINE, EMBASE, CINAHL, the Cochrane Central Register of Controlled Trials and Web of Science up to September 2017. Eligibility criteria: RCTs investigating the impact of exercise on MRI-assessed articular cartilage in people over 18 years of age. Results: We included nine trials, including a total of 14 comparisons of cartilage morphometry, morphology and composition outcomes, of which two included participants at increased risk of knee OA and 12 included participants with knee OA. In participants at increased risk, one study comparison reported no effect on cartilage defects and one had positive effects on glycosaminoglycans (GAG). In participants with OA, six study comparisons reported no effect on cartilage thickness, volume or defects; one reported a negative effect and one no effect on GAG; two reported a positive effect and two no effect on collagen. Conclusions: Knee joint loading exercise seems to not be harmful for articular cartilage in people at increased risk of, or with, knee OA. However, the quality of evidence was low, including some interventions studying activities considered outside the therapeutic loading spectrum to promote cartilage health.